Ants of Colombia X. Acanthognathus with the description of a new species (Hymenoptera: Formicidae) - GALVIS, JUAN PABLO; FERNÁNDEZ, FERNANDO (Revista Colombiana de Entomología, 2009)
A new species in the ant genus Acanthognathus, A. laevigatus n. sp., is described from the Pacific region of Colombia (Barbacoas, Nariño). A key to identify the eight species of Acanthognathus known to occur in the Neotropics is provided. In addition, the species A. brevicornis is recorded for the first time for Colombia.